Differential Proteomic Profiles of Pleurotus ostreatus in Response to Lignocellulosic Components Provide Insights into Divergent Adaptive Mechanisms - Xiao, Qiuyun; Ma, Fuying; Li, Yan; Yu, Hongbo; Li, Chengyun; Zhang, Xiaoyu (Frontiers in Microbiology, 2017)
Pleurotus ostreatus is a white rot fungus that grows on lignocellulosic biomass by metabolizing the main constituents. Extracellular enzymes play a key role in this process. During the hydrolysis of lignocellulose, potentially toxic molecules are released from lignin, and the molecules are derived from hemicellulose or cellulose that trigger various responses in fungus, thereby influencing mycelial growth. In order to characterize the mechanism underlying the response of P.ostreatus to lignin, we conducted a comparative proteomic analysis of P. ostreatus grown on different lignocellulose substrates. In this work, the mycelium proteome of P. ostreatus grown in liquid minimal medium with lignin, xylan, and carboxymethyl cellulose (CMC) was analyzed using the complementary two-dimensional gel electrophoresis (2-DE) approach; 115 proteins were identified, most of which were classified into five types according to their function. Proteins with an antioxidant function that play a role in the stress response were upregulated in response to lignin. Most proteins involved in carbohydrate and energy metabolism were less abundant in lignin. Xylan and CMC may enhanced the process of carbohydrate metabolism by regulating the level of expression of various carbohydrate metabolism-related proteins. The change of protein expression level was related to the adaptability of P. ostreatus to lignocellulose. These findings provide novel insights into the mechanisms underlying the response of white-rot fungus to lignocellulose.